Quantitative characterization reveals three types of dry-sensitive corneal afferents: pattern of discharge, receptive field, and thermal and chemical sensitivity - Hirata, Harumitsu (American Physiological Society, 2012)
This study reveals that the cold-sensitive (CS) + dry-sensitive (DS) corneal afferents reported in a previous study consist of two types: 1) low threshold (LT)-CS + DS neurons with <1°C cooling sensitivity, and 2) high threshold (HT)-CS + DS neurons with a wide range of cooling sensitivities (∼1–10°C cooling). We also found DS neurons with no cooling sensitivity down to 19°C [cold-insensitive (CI) + DS neurons]. LT-CS + DS neurons showed highly irregular discharge patterns during the dry cornea characterized by numerous spiking bursts, reflecting small temperature changes in the cornea. Their receptive fields (RFs) were mainly located in the cornea's center, the first place for tears to ebb from the surface and be susceptible to external temperature fluctuations. HT-CS and CI + DS neurons showed a gradual rise in firing rate to a stable level over ∼60 s after the dry stimulus onset. Their RFs were located mostly in the cornea's periphery, the last place for tears to evaporate. The exquisite sensitivity to cooling in LT-CS + DS neurons was highly correlated with heat sensitivity (∼45°C). There was a perfect correlation between noxious heat sensitivity and capsaicin responsiveness in each neuron type. The high sensitivity to noxious osmotic stress was a defining property of the HT-CS and CI + DS neurons, while high sensitivity to menthol was a major characteristic of the LT-CS + DS neurons. These observations suggest that three types of DS neurons serve different innocuous and nociceptive functions related to corneal dryness.